2015
DOI: 10.1002/clen.201400508
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chlorophene in a Backwater Stream in Kerala (India) and its Sonochemical Degradation Studies

Abstract: Identification of Chlorophene in a Backwater Stream in Kerala (India) and its Sonochemical Degradation StudiesChlorophene, a chlorinated phenolic compound and a well-known emerging pollutant due to its extensive use as an antimicrobial agent, has been identified in a local backwater stream using liquid chromatography quadrupole time of flight MS (LC-Q-TOF-MS). The concentration of chlorophene has been calculated as 6 Â 10 À7 mol L À1(0.132 ppm). In order to develop a suitable treatment protocol, ultrasound med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…The analytical parameters obtained in this study are summarized in Table 1. The results obtained meet the concentration detected in a backwater stream in Kerala (India) [7] and in activated sludge sewage [9] by HPLC-MS and GC-MS. Additionally, the immobilized enzyme withstood 35 regeneration cycles by using 0.1 M NaOH before any significant loss of recognition capacity was observed. Currently, there is a lack of biosensors that address the detection of CP, since the analytical tools have been mainly limited to chromatographic techniques.…”
Section: Spr Measurements: Chlorophene Detectionsupporting
confidence: 79%
See 2 more Smart Citations
“…The analytical parameters obtained in this study are summarized in Table 1. The results obtained meet the concentration detected in a backwater stream in Kerala (India) [7] and in activated sludge sewage [9] by HPLC-MS and GC-MS. Additionally, the immobilized enzyme withstood 35 regeneration cycles by using 0.1 M NaOH before any significant loss of recognition capacity was observed. Currently, there is a lack of biosensors that address the detection of CP, since the analytical tools have been mainly limited to chromatographic techniques.…”
Section: Spr Measurements: Chlorophene Detectionsupporting
confidence: 79%
“…The presence of this emerging pollutant has been commonly detected by high performance liquid chromatography mass spectrometry (HPLC-MS) [4] and gas chromatography mass spectrometry (GC-MS) [3], powerful analytical methods for detecting and quantifying trace amounts of compounds. For instance, Rayaroth et al (2015) [7] identified the presence of chlorophene in a backwater stream using the liquid chromatography quadrupole time of flight MS (LC-QTOF-MS), with a C18 column set at 35 • C and a gradient elution of acetonitrile:formic acid in water (0.1%). Meanwhile, Chen et al (2018) [11] established the quantification of CP using an HPLC instrument with a UV absorbance detector, an SB-C18 column and a mixture of formic acid as a mobile phase and methanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of some micropollutants on the degradation of methylparaben has also been investigated by this high-resolution mass spectrometric technique (Sasi et al 2015). The advantage of using this technique over other mass spectrometric technique is in the identification of unknown compound as it offers the elemental composition and the possible structure from the software itself (Rayaroth et al 2015b).…”
Section: Sonoelectrochemical Methodsmentioning
confidence: 99%
“…There are several mass spectrometric techniques for the trace-level detection of micropollutants from water, such as triple quadrupole systems, time of flight and Orbitrap TM instruments, and their hybrid configurations, quadrupole time of flight, ion trap-Orbitrap or quadrupole-Orbitrap mass spectrometers, etc. (Rayaroth et al 2015b;Sirtori et al 2014).…”
Section: Introductionmentioning
confidence: 97%